Identifikasi Bakteri Salmonella pada Jajanan Sekolah di Wilayah Kerja Puskesmas Klego - Virdianita, Alreza; Ristiawati, Ristiawati; Fitriyani, Nur Lu’lu (JURNAL LITBANG KOTA PEKALONGAN, 2023)
Background: Typhus abdomonalis is an acute infectious disease caused by Salmonella thypi bacteria. The highest prevalence of typhoid fever in the area of Klego Health Center is children at group of 3-19 year old. School-age children tend to pay less attention to personal hygiene because they do not know that snacking carelessly can cause the spread of various diseases. The purpose of this research is to explore salmonella bacteria in school snacks.Methods: This is a descriptive research. The data collection technique was in the form of laboratory observation with the object of research identifying Salmonella in school snacks. The population in this study were school snacks in the working area of the Klego Health Center with the sampling technique using purposive sampling .Results: The results of this study showed that out of 18 samples, 2 samples (S2C and S2D) were positively contaminated with Salmonella bacteria.Conclusion: Out of 18 samples of school snacks, 2 of them were positive for Salmonella bacteria. For this reason, it is necessary to carry out training classes and routine screening of food tests by the Pekalongan City Health Office.  Keywords: Salmonella, school snacks, foodborne illness